A psychometric investigation of the sleep, circadian rhythms, and mood (SCRAM) questionnaire. (1st February 2019) - Byrne, Jamie E. M.; Bullock, Ben; Brydon, Aida; Murray, Greg
ABSTRACT: The sleep, circadian rhythms, and mood (SCRAM) questionnaire (Byrne, Bullock et al., 2017) was designed to concurrently measure individual differences in three clinically important functions: diurnal preference, sleep quality, and mood. The 15-item questionnaire consists of three 5-item scales named Morningness, Good Sleep, and Depressed Mood . The overarching aim of the current project was to investigate the validity and reliability of the questionnaire. Here, we report on associations investigated in three data sets. Study 1 ( N  = 70, 80% females) was used to examine the test–retest reliability of the questionnaire, finding strong test–retest reliability of the three scales over a 2-week period ( r 's ranging from 0.73 to 0.86). Study 2 ( N  = 183, 80% females) enabled us to examine the construct validity of the SCRAM scales against well-validated self-report measures of diurnal preference, sleep quality, and depression. Strong correlations were found between each SCRAM scale and their respective measure in bivariate analyses, and associations were robust after the inclusion of the remaining two SCRAM scales as predictors in regression analyses. Data from Study 3 ( N  = 42, 100% males) were used to measure the extent to which SCRAM scores correlated with objective measures of sleep–wake behavior using actigraphy. Morningness was found to be related to earlier sleep onset and offset times, and Good Sleep was related to higher sleep efficiency but to no other measures of sleep quality; Depressed Mood was not related to actigraphy measures. The findings provide provisional support for construct validity and reliability of the SCRAM questionnaire as a measure of diurnal preference, sleep quality, and depressed mood. Future research into the psychometrics of SCRAM should test the questionnaire's discriminant and predictive validity in clinical samples.